Safety of atorvastatin in Asian patients within clinical trials - Chan, Juliana C. N.; Kong, Alice P. S.; Bao, Weihang; Fayyad, Rana; Laskey, Rachel (Cardiovascular therapeutics, 2016)
Summary Introduction Data on statin safety in Asian patients are limited compared with evidence from Western populations. Aim This study assessed atorvastatin safety among Asian patients enrolled in 58 randomized clinical trials. Methods Data from 52 short‐term trials (median exposure 4–72 weeks) and six long‐term cardiovascular outcomes trials (median exposure 3.1–4.9 years) conducted across the atorvastatin 10–80‐mg dose range were analyzed retrospectively to assess the incidence of safety endpoints. Results A total of 77 952 patients were identified (49 974 received atorvastatin), among whom 3191 were Asian (2519 received atorvastatin). In the short‐term trials, the incidence of all‐causality adverse events (AEs) and serious AEs (SAEs) in Asian patients treated with atorvastatin was similar to or lower than that observed with other statins or placebo, and discontinuations due to treatment‐related AEs/SAEs were infrequent (2.0% across all doses). These observations were confirmed in the long‐term trials. Treatment‐related SAEs were rare (n = 4) among Asian patients receiving atorvastatin. No cases of rhabdomyolysis were observed in atorvastatin‐treated Asian patients, and the incidence of myalgia was 1.8% in the short‐term studies and 6.7% in the long‐term trials. Elevations (>3× the upper limit of normal) in liver transaminases were observed in ~2% of Asian patients receiving atorvastatin; renal AEs occurred in <2%. Conclusion The incidence of AEs/SAEs with atorvastatin 10–40‐mg in patients of Asian origin was low and comparable to placebo. Further evaluation of atorvastatin 80‐mg is required owing to the limited number of Asian patients (n = 281; 11.2%) who received this dose.